Mapping educational innovation and knowledge dissemination: a global bibliometric study - M. Fahli Zatrahadi; Yahya Muhammed Bah; Istiqomah Istiqomah; Saikou Gassama; Elrisfa Magistarina; Edris bin Aden; Kemo Juwara; Silas Oghenemaro Emovwodo; Haruna Badjie (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
From 2023 to 2025, 1,034 publications were examined for academic knowledge diffusion and educational innovation.  This bibliometric analysis uses VOSViewer for data recovery, pre-processing, network extraction, normalization, and visualization.  Due to its importance in educational innovation, many research clusters focus on "information dissemination".  The educational innovation ecosystem comprises higher education social media, knowledge management, and sustainability.  This analysis also finds clusters linking educational innovation to knowledge management, psychology, health workers, and sustainability.  In this study, digital technology, architecture, and organizational intelligence determine how digital connectivity increases educational creativity.  Technology like short films helps students understand difficult concepts.  Educational innovation research may focus on machine learning, social media, and information distribution, according to keywords and trends.  This study suggests digital tools, data-driven initiatives, and inclusive knowledge exchange for educational innovation.  These findings could inspire new learning and knowledge distribution initiatives by academics, legislators, and educators.